Stimulating investment and growth in the Philippines: The need for first-order market reforms - Desiree A. Desierto; Geoffrey M. Ducanes (University of the Philippines, School of Economics (UPSE), 2011)
We show that the most important barriers to investment and growth in the Philippines are structural and institutional problems that are characteristic of limited access societies, which can be more effectively and efficiently overcome by prioritizing 'first-order' market reforms that increase competition and openness, rather than by government regulations that enforce against the distortions.
Keywords: 330; Auslandsinvestition; Wirtschaftswachstum; Institutionelle Infrastruktur; Wirtschaftsreform; Internationaler Wettbewerb; Handelsliberalisierung; Philippinen